One New Species of the Genus Stenus Latreille (Coleoptera, Staphylinidae) from Hubei, China - Lv, Wei-Xiang; Zhao, Cai-Yun; Zhou, Hong-Zhang (Zootaxa, 2018)
This paper treats the S. cephalotes group and S. indubius group (Coleoptera: Steninae) from China and includes description of one new species: Stenus wujiei Lv, Zhao & Zhou, sp. nov. from Hubei, China. S. detestabilis Puthz and S. hui Tang & Puthz are newly recorded to Hubei Province. Their diagnostic characters are illustrated.